2017
DOI: 10.1038/cddis.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-treating fields elicit a conditional vulnerability to ionizing radiation via the downregulation of BRCA1 signaling and reduced DNA double-strand break repair capacity in non-small cell lung cancer cell lines

Abstract: The use of tumor-treating fields (TTFields) has revolutionized the treatment of recurrent and newly diagnosed glioblastoma (GBM). TTFields are low-intensity, intermediate frequency, alternating electric fields that are applied to tumor regions and cells using non-invasive arrays. The predominant mechanism by which TTFields are thought to kill tumor cells is the disruption of mitosis. Using five non-small cell lung cancer (NSCLC) cell lines we found that there is a variable response in cell proliferation and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 42 publications
10
127
0
Order By: Relevance
“…49 This suggests that stalled replication fork stabilization confers resistance to replication stress-inducing chemotherapeutics but because of the general suppression of a host of genes and proteins involved in replication fork maintenance and stability, checkpoint control and DNA repair pathways, TTFields exposure may overcome such resistance. Indeed the results herein provide a rationale for the additive to synergistic effects of TTFields seen in earlier preclinical reports 10,[12][13][14][15] with chemotherapeutic drugs such as paclitaxel, cisplatin, gemcitabine, doxorubicin, 5-FU, cyclophosphamide, DTIC, and Irinotecan which are known to primarily increase replication stress but not directly affect mitosis. [7][8][9][10][11] DNA replication is a mandatory and prerequisite step for mitosis.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…49 This suggests that stalled replication fork stabilization confers resistance to replication stress-inducing chemotherapeutics but because of the general suppression of a host of genes and proteins involved in replication fork maintenance and stability, checkpoint control and DNA repair pathways, TTFields exposure may overcome such resistance. Indeed the results herein provide a rationale for the additive to synergistic effects of TTFields seen in earlier preclinical reports 10,[12][13][14][15] with chemotherapeutic drugs such as paclitaxel, cisplatin, gemcitabine, doxorubicin, 5-FU, cyclophosphamide, DTIC, and Irinotecan which are known to primarily increase replication stress but not directly affect mitosis. [7][8][9][10][11] DNA replication is a mandatory and prerequisite step for mitosis.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, using nucleotide analogs, newly synthesized DNA length was measured and confirmed that TTFields decreases the speed of DNA replication (Fig 1, BÀD), which suggests that TTFields induces replication stress. Although these results do not distinguish between co-directional and head-on collisions, it is clear that under TTFields treatment, these collisions are not resolved properly to facilitate the proper progression of replication given reduced expression of the FA pathway 15 and MCM genes (Fig 1, A) upon TTFields exposure. 15,26,27 Changes in DNA topology during collisions between replication and transcription machineries cause DNA-RNA hybrid structures called R-loops to form.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations